Carnosol Induces p38-Mediated ER Stress Response and Autophagy in Human Breast Cancer Cells - Alsamri, Halima; Alneyadi, Aysha; Muhammad, Khalid; Ayoub, Mohammed Akli; Eid, Ali; Iratni, Rabah (Frontiers in Oncology, 2022)
We recently reported that carnosol induces ROS-dependent autophagy and apoptosis in breast cancer cells. We also reported that carnosol inhibits breast cancer cell migration, invasion, and in ovo tumor growth, as well as targets STAT3, PCAF, and p300 to proteasome degradation. Here, we investigated the molecular mechanisms underlying its anti-malignant activity in breast cancer. We report that carnosol induces a ROS-dependent type I and type II programmed cell death (PCD-I or PCD-II, respectively), which occurred independently of each other. Indeed, chemical inhibition of autophagy had no effect on the induction of apoptosis, evident by the absence of cleaved PARP. Electron microscopy revealed that carnosol-treated cells exhibited enlarged endoplasmic reticulum, characteristic of ER stress. Markers of the three unfolded protein response pathways (PERK, IRE-1 α, and ATF6), namely ATF4, CHOP, phospho-IRE-1α, XBP1S, and cleaved ATF6 were upregulated in a ROS-dependent manner. In addition, carnosol induced a ROS-dependent activation of p38MAPK, increased the overall level of protein polyubiquitination, and targeted mTOR protein to proteasome degradation. Interestingly, inhibition of p38MAPK, by SB202190 and 203580, reduced cell death, selectively blocked the induction of IRE-1α and ATF6 UPR sensors and inhibited autophagy. In addition, inhibition of p38 reduced the carnosol-induced polyubiquitination and rescued mTOR, PCAF, and STAT3 from proteasomal degradation. Importantly, activation of PERK sensors and induction of apoptosis occurred independently of p38 activation. Taken together, our results suggest that ROS-dependent induced-ER stress contributes to carnosol-induced apoptotic and autophagic cell death in breast cancer cells, and further confirm that carnosol is a promising agent for breast cancer therapy.